Sportsmanship in sport with athlete perspective - Ilyas Gorgut; Erkut Tutkun (ROL Spor Bilimleri Dergisi)
The study aims to determine the athletes’ views on sportsmanship. In the study, qualitative research method and phenomenology design was preferred. The sampling group of the study consists of 15 athletes determined by the easily accessible case sampling method. Individual interviews were conducted with the athletes within the scope of semi-structured interview technique lasting an average of 25 minutes. Descriptive and content analysis methods were applied to the transcribed participant statements. As a result, sportsmen define sportsmanship as acting in accordance with the rules and fighting within the scope of fair play. Having or not having sportsmanship behaviour has positive or negative effects on all segments in the field and the competition environment, the circle of friends, especially the family and the coach, are the relevant stakeholders affecting sportsmanship. Finally, unsportsmanlike behaviours are seen due to reasons such as coach behaviours, provocation of the rival team, injury, etc.